Kondisi Jalan Menuju Kawasan Wisata Sarasah Pontong di Nagari Dalko: Pengaruh Terhadap Pariwisata - manaruko, rino; Feni Deanof Putri; Doni Adriansyah; Rani Nabilla Putri; Clarissa Amanda; Apri Yenni; Muhammad Farhan; Erlangga Arzico (Manaruko: Jurnal Pengabdian Masyarakat, 2024)
The condition of the Sarasah Pontong road in Nagari Dalko, Sumatera Barat, significantly influences the potential of the tourism sector. The condition includes poor road conditions, high traffic, and limited parking, making the accessibility of the area difficult. To improve accessibility and the duration of the road, several strategies are proposed. First, improving road conditions by incorporating various factors to prevent deterioration and make the road more stable. Second, improving road safety by providing information about road conditions and promoting physical safety measures. This comprehensive study provides valuable insights for planning and implementation strategies in the Sarasah Pontong area